Effectiveness of Strategic Intervention Material (SIM) in Improving Filipino Student’s Performance in Science and Mathematics: A Meta-analysis - Borabo, Jonnell; Dio, Ryan V. (Journal of Basic Education Research, 2025)
Purpose of the study: This meta-analysis aimed to determine the effectiveness of Strategic Intervention Materials (SIM) in improving Filipino students' science and mathematics performance. Methodology: Fifteen eligible studies from three databases: Google Scholar, Crossref, and Semantic Scholar were chosen using Harzing’s Publish and Perish tool. The studies underwent meta-analysis using the Jamovi Tool. Main Findings: Using Strategic Intervention Material has a large average effect size (ES = 1.60) with most of the studies obtaining positive effect sizes (87%). In connection, the moderator analysis showed paper-based SIM has a relatively larger effect size than digital SIM, elementary level obtained a larger effect size than Junior and Senior High and science has larger effect size than mathematics. Nevertheless, all moderators obtained large effect sizes which means SIM is an effective classroom intervention across the different types, grade levels and content areas. Novelty/Originality of this study: This research introduces new insights into classroom intervention by exploring the use of Strategic Intervention Material (SIM) which was conceptualized and commonly used in the Philippines. The study opens discourse on the use of SIM to improve the learners’ science and mathematics achievement for possible adoption on a global scale.